Factors Affecting Accounting Conservatism in Indonesia - Noviyanti, Anita; Agustina, Linda (Universitas Negeri Semarang, 2021)
The purpose of this study is to analyze and obtain empirical evidence regarding the role of managerial ownership, institutional ownership, independent commissioners, leverage, liquidity, growth opportunity, and litigation risk that affect accounting conservatism. The population in this research is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017 with 147 companies. The sample in this research was selected through a purposive sampling technique so that the final sample was obtained by 37 companies with 111 units of analysis. Data collection techniques use documentation techniques. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis which uses multiple linear regression analysis with IBM SPSS 22. The results of the research indicate that independent commissioners have a positive and significant effect on accounting conservatism. Institutional ownership has a negative and significant effect on accounting conservatism while managerial ownership, leverage, liquidity, growth opportunity, and litigation risk do not affect accounting conservatism. This study concludes that institutional ownership and independent commissioners influence accounting conservatism. Keywords: Accounting Conservatism; Good Corporate Governance; Leverage; Liquidity; Growth Opportunity; Litigation Risk